1997
DOI: 10.1073/pnas.94.11.5923
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity associated with dual actions of homocysteine at the N -methyl- d -aspartate receptor

Abstract: Severely elevated levels of total homocysteine (approximately millimolar) in the blood typify the childhood disease homocystinuria, whereas modest levels (tens of micromolar) are commonly found in adults who are at increased risk for vascular disease and stroke. Activation of the coagulation system and adverse effects of homocysteine on the endothelium and vessel wall are believed to underlie disease pathogenesis. Here we show that homocysteine acts as an agonist at the glutamate binding site of the N-methyl-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
554
2
25

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 788 publications
(600 citation statements)
references
References 35 publications
19
554
2
25
Order By: Relevance
“…This suggests a non-vascular mechanism by which folate intake may be related to the development of AD. Another nonvascular mechanism is supported from evidence that homocysteine may cause direct toxicity to neuronal cells [41]. Nonhomocysteine mechanisms involving methylation reactions in the brain [42] have also been postulated to explain the association between folate intake and AD development.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a non-vascular mechanism by which folate intake may be related to the development of AD. Another nonvascular mechanism is supported from evidence that homocysteine may cause direct toxicity to neuronal cells [41]. Nonhomocysteine mechanisms involving methylation reactions in the brain [42] have also been postulated to explain the association between folate intake and AD development.…”
Section: Discussionmentioning
confidence: 99%
“…Neither did MK801ϩ, an inhibitor of NMDA receptors. This latter result was somewhat surprising, as Hcys can serve as a ligand for NMDA receptors (Kim and Pae, 1996;Lipton et al, 1997) and cardiac NC cells express NMDA receptors (Brauer and Rosenquist, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Disease susceptibility is partly genetically determined, however the underlying molecular mechanisms of MS pathogenesis remain unidentified [11]. In vitro studies have demonstrated the ability of Hcy to induce neurotoxicity through over-stimulation of N-methyl-d-aspartate (NMDA) receptors resulting in neuronal damage due to excessive Ca 2+ influx and induction of reactive oxygen species [12]. MTHFR deficiency is the most common genetic cause of hyperhomocysteinemia [13].…”
Section: Discussionmentioning
confidence: 99%